Dyslipidaemia and inflammation are risks for subclinical atherosclerotic vascular disease among chronic kidney failure patients in South Africa - S. O. Oguntola; M.O. Hassan; R. Duarte; C. Dickens; T. Dix-Peek; T. Snyman; K. Moodley; G. Olorunfemi; A. Vachiat; P. Manga; S. Naicker (PLoS ONE, 2025)
Background Chronic kidney disease (CKD) is associated with generalized inflammation. The presence of CKD-related (non-traditional) cardiovascular disease (CVD) risk factors such as inflammation, oxidative stress and uraemic toxins worsen the CVD. A distinct form of lipoprotein alteration known as uraemic dyslipidaemia, characterized by normal low-density lipoprotein (LDL), reduced high density lipoprotein (HDL) and elevated triglyceride and lipoprotein (a) has been described in CKD. The combination of all these factors increase the cardiovascular risk in CKD patients. We evaluated the relationship of lipoprotein and inflammatory biomarkers to atherosclerotic vascular disease (AsVD) among stage 3 CKD, end stage kidney disease (ESKD) patients on continuous ambulatory peritoneal dialysis (CAPD) and haemodialysis (HD) and kidney transplant recipients (KTRs). Methods This was a cross-sectional study of 40 adult (18–65 years) non-diabetic stage 3 CKD patients, 40 CAPD and 40 HD patients, 41 KTRs and 41 age- and sex-matched healthy controls. Socio-demographic and cardiovascular risk factors were documented and serum samples were analysed for inflammatory and lipoprotein markers. Echocardiography was performed and carotid intima media thickness (CIMT) was measured in all participants. Results The overall prevalence of AsVD was 52.8% in the study population, with the highest burden of inflammation present in CAPD patients. Significantly increased levels of hsCRP, pentraxin-3, Lp(a) and Lp-PLA2 were seen in CAPD, compared to controls. Older age, male gender, reduced high-density lipoprotein (HDL-C) and elevated Lp(a) levels were independently associated with AsVD. Conclusion The burden of inflammation and lipoprotein abnormalities was greatest among end stage kidney disease (ESKD) patients and was the highest in CAPD patients. Lipoprotein(a) independently predicted AsVD.